2017
DOI: 10.1038/s41598-017-14074-9
|View full text |Cite
|
Sign up to set email alerts
|

The antimalarial activity of the pantothenamide α-PanAm is via inhibition of pantothenate phosphorylation

Abstract: The biosynthesis of the major acyl carrier Coenzyme A from pantothenic acid (PA) is critical for survival of Plasmodium falciparum within human erythrocytes. Accordingly, a PA analog α-PanAm showed potent activity against blood stage parasites in vitro; however, its efficacy in vivo and its mode of action remain unknown. We developed a new synthesis route for α-PanAm and showed that the compound is highly effective against blood stages of drug-sensitive and -resistant P. falciparum strains, inhibits developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…The 1,2,3‐triazole ring is among the most commonly used scaffolds in drugs . The triazole derivatives 1 and 2 are stable in serum, show excellent antiplasmodial activity, are not toxic to human cells and have a new mode of action relative to clinical drugs, making them attractive hits for the development of novel antimalarials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,2,3‐triazole ring is among the most commonly used scaffolds in drugs . The triazole derivatives 1 and 2 are stable in serum, show excellent antiplasmodial activity, are not toxic to human cells and have a new mode of action relative to clinical drugs, making them attractive hits for the development of novel antimalarials.…”
Section: Discussionmentioning
confidence: 99%
“…Pantothenamides were later found to be metabolically activated by enzymes of the coenzyme A (CoA) biosynthetic pathway in P . falciparum . This may not only affect CoA biosynthesis but the resulting metabolites are also inferred to inhibit downstream CoA‐utilizing pathways, leading to lethal effects on P .…”
Section: Introductionmentioning
confidence: 99%
“…A mutant, cab1 ts , which produces a kinase enzyme with glycine 351 substituted to serine, was found to be viable at 30°C but is completely inviable at 37°C (8). Biochemical assays using purified WT and mutated Cab1p enzymes showed that the G351S substitution results in ϳ94% loss of enzyme activity (9). Recent studies showed that the pantothenate analog ␣-PanAm 2 inhibits yeast growth in a pantothenic acid dose-dependent manner (9).…”
mentioning
confidence: 99%
“…Biochemical assays using purified WT and mutated Cab1p enzymes showed that the G351S substitution results in ϳ94% loss of enzyme activity (9). Recent studies showed that the pantothenate analog ␣-PanAm 2 inhibits yeast growth in a pantothenic acid dose-dependent manner (9). The MIC 50 of the compound was found to be ϳ4 times higher in medium supplemented with 1 M pantothenic acid (MIC 50 ϳ 7.6 g/ml) compared with medium with 100 nM pantothenic acid (MIC 50 ϳ 1.9 g/ml) (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation